Impacts of Soil Contamination on the Response of Piles Foundation under a Combination of Loading - Karkush, M. O. (Engineering, Technology & Applied Science Research, 2016)
The behavior of single piles driven into contaminated clayey soil samples subjected to a combination of static axial and cyclic lateral loadings have been studied in this research. A laboratory model was manufactured especially for studying such behavior. A solid circular cross sectional area pile of diameter 19 mm and made from aluminum, the pile was embedded into the soil with an eccentricity to embedded length (e/L) ratio of 0.334. The intact soil samples and industrial wastewater were obtained from the center of Iraq. The industrial wastewater is a byproduct disposed from Musayib thermal electric power plant. The intact clayey soil samples were synthetically contaminated with four percentages of 10, 20, 40 and 100% from the weight of water used in the soaking process which continued for a period of 30 days. The different percentages of contaminant concentrations have significant effects on the lateral load-displacement relation of the piles subjected to a combination of axial and lateral loadings. The vertical displacement under the same vertical load increased by 5–95%, the axial strength of piles decreased by 10–34% and the lateral-bearing capacity of the piles decreased by 10–34% with increasing the percentage of contamination from 10 to 100%. The ratio of permanent lateral displacement to the total lateral displacement was increased by 23–27% when the concentration of contaminant increased by 10-100%. Generally, the application of axial loading increases the lateral-bearing capacity of piles, and reduces the total lateral displacement.